The Role of Parent-Teacher Partnership in Promoting Numeracy Skills Among Primary School Students - Ana Lorraine B. Bubuli; Maridel D. Macapobre (CV. Ridwan Publisher, 2023)
This study aimed to explore the perspectives of teachers and parents regarding parent-teacher partnerships in promoting numeracy skills. A qualitative research design was used, and data were collected through focus group discussions with ten teachers and ten parents from a primary school in the Division of Toledo City. The data were analyzed thematically, and five themes emerged: the importance of parent-teacher partnerships, communication, parental involvement, teacher support, and resources. The findings indicated that parent-teacher partnerships were crucial in promoting numeracy skills, and effective communication was essential for building trust and collaboration. Participants emphasized the need for parental involvement, including regular attendance at parent-teacher meetings and supporting numeracy development at home. Teacher support was also identified as crucial, including the provision of clear explanations of numeracy concepts and strategies. Finally, participants highlighted the importance of having access to resources, including instructional materials and professional development opportunities for teachers and parents. These findings provide insights into the factors that contribute to successful parent-teacher partnerships in promoting numeracy skills and highlight the importance of collaboration and communication between parents and teachers.